Risk-adjusted option-implied moments - Felix Brinkmann; Olaf Korn (University of Cologne, Centre for Financial Research (CFR), 2014)
Option-implied moments, like implied volatility, contain useful information about an underlying asset's return distribution, but are derived under the risk-neutral probability measure. This paper shows how to convert risk-neutral moments into the corresponding physical ones. The main theoretical result expresses moments under the physical probability measure in terms of observed option prices and the preferences of a representative investor. Based on this result, we investigate several empirical questions. We show that a model of a representative investor with CRRA utility can explain the variance risk premium for the S&P500 index but fails to capture variance and skewness risk premiums simultaneously. Moreover, we present methods to estimate forward-looking market risk premiums and investors' disappointment aversion implied in market prices.
Keywords: G13; G17; C51; C53; 330; option-implied moments; risk adjustment; variance risk premium; market risk premium; disappointment aversion